2022
DOI: 10.3389/fmicb.2022.979558
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence, characteristics, and future prospects of IncX3 plasmids: A review

Abstract: IncX3 plasmids are narrow host range plasmids mostly found in Enterobacteriaceae with great conjugation ability, high stability, no fitness cost, and the ability to improve biofilm formation in their bacterial hosts. IncX3 plasmids have spread swiftly, primarily in several nations and among different species over the last 10 years. blaNDM, blaKPC, and blaOXA-181 are the carbapenemase genes carried by IncX3 plasmids. Among them, blaNDM is often located on the IncX3 plasmid, which is deemed as the primary vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
1
25
2
Order By: Relevance
“…In our study, most IncX plasmids were IncX3, deemed the primary vehicle for bla NDM transmission. IncX3 plasmids have been found to spread rapidly among different species without tness cost, with excellent conjugation ability, high stability, and the ability to improve bio lm formation in their bacterial hosts [45]. Given that IncX3 plasmids were found among most of the bla NDM -carrying E. coli in our study, we speculate that IncX is the main host for bla NDM [46].…”
Section: Discussionmentioning
confidence: 67%
“…In our study, most IncX plasmids were IncX3, deemed the primary vehicle for bla NDM transmission. IncX3 plasmids have been found to spread rapidly among different species without tness cost, with excellent conjugation ability, high stability, and the ability to improve bio lm formation in their bacterial hosts [45]. Given that IncX3 plasmids were found among most of the bla NDM -carrying E. coli in our study, we speculate that IncX is the main host for bla NDM [46].…”
Section: Discussionmentioning
confidence: 67%
“…According to Wang et al (2018), IncX3 plasmids had similar or higher conjugation frequencies than IncFII plasmids at 30°C and 37°C, suggesting that the plasmid replicon types are associated with temperature in the horizontal transfer of antibiotic resistance genes (Wang et al, 2018). IncX3 plasmids can be transferred between various Enterobacterial species over a wide temperature range (Guo et al, 2022). Previous studies reported higher frequencies of plasmid delivery to recipients at 30°C than at 25°C or 37°C (Liakopoulos et al, 2018;Walsh et al, 2011), and that a temperature of 30°C increases conjugation (Anaı¨s Potron et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Among the incompatible plasmid groups associated with carbapenemase genes in Enterobacterales (Katlego Kopotsa et al, 2019), the bla KPC gene is harbored by IncF, IncI2, IncX, IncA/C, IncR, and ColE1 , whereas bla NDM is mainly located on plasmids of the IncX3 type (Liu et al, 2021). The IncX3 plasmid transports and spreads carbapenemase genes (bla NDM , bla KPC , and bla OXA−48 -like), particularly bla NDM (Guo et al, 2022). In our study, IncF was dominant for the bla KPC gene, and IncX3 was predominant for bla NDM (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that with further study and discovery, PDPs could be exploited to manipulate the dynamics of conjugative plasmid mobility, and thus the spread of antibiotic resistance genes in high-risk environments. PDPs may be particularly applicable to controlling epidemics of plasmid acquired resistance, for example the current epidemic of carbapenem-resistant Enterobacteriaceae mobilized by IncX3 conjugative plasmids [52][53][54] .…”
Section: Discussionmentioning
confidence: 99%